RISK ASSESSMENT AND PREDICTION OF THE POSSIBILITY OF ACUTE TOXIC EFFECTS ON WORKERS WHEN APPLY- ING OBERON RAPID 240 SC - Tkachenko , Inna; Antonenko , Anna (The Ukrainian Scientific Medical Youth Journal, 2021)
the issue of uncontrolled pesticides application is quite acute in the system of state control over the use of chemical plant protection products and is of a global nature. Indeed, the dangerous effect of chemicals is a potential toxic effect on professional and non-professional contingents. Therefore, the study and forecasting of possible risks of negative effects of pesticides is an integral part of their implementation in the practical activities of agricultural and private farms. The aim was to predict the occurrence of acute toxic effects on workers involved in the treatment of crops with formulation based on the new insecticide spiromesifen and a representative of avermectins, abamectin. Materials and methods. To calculate the coefficients of possible inhalation poisoning, the physic-chemical properties and consumption rates of the studied active ingredients of the Oberon Rapid 240 SC formulation, the methodical approaches from State Standard 8.8.1.002-98 wase used, and to determine the possibility of acute toxic effects, taking into account the selectivity of their action, we used the Sergeev’s S.G. method, taking into account two ways of potential entry of chemicals into the body – inhalation and dermal. Results. According to the "Hygienic classification of pesticides by the degree of hazard", spiromesifen and abamectin, as well as formulation based on them, belong to the Ⅳth hazard class according to the coefficient of possible inhalation poisoning, which was less than 0.5. In terms of inhalation and dermal coefficients of selectivity of action, the studied compounds were classified as substances with a high selectivity of action, except for the value of the coefficient of inhalation action of abamectin, which was less than 100 and made it possible to classify the compound as substances with a relatively low selectivity of action. Conclusions. The obtained data indicate a low possibility of acute poisoning when using formulations based on insecticides – spiromesifene and abamectin, as well as their relative safety in the occurrence of acute toxic effects when inhaled and in contact with the skin.